Analisis Yuridis terhadap Urgensi Akta Autentik Notaris dalam Perjanjian Pengalihan Hak Cipta - Usak, Usak; Sengi, Ernest; Laike, Reli Jevon (Wajah Hukum, 2024)
The purpose of this research is to examine importance of setting up copyright transfer agreement and to analyze juridically the urgency of an authentic notary deed in a copyright transfer agreement. The research method used is normative legal research with statute approach. Results of study found that the importance of setting up copyright transfer agreement is guarantee of legal protection of economic rights from creator; guarantee of legal protection to non-creator parties who obtain economic rights as a result of transfer of copyright in whole or in part; and minimize disputes in transfer of Copyright. The urgency of Notary authentic deed in a copyright transfer agreement are: first, Notary profession is bound by law, so it has credibility in making an authentic copyright transfer deed; second, authentic notary deed serves as a means of proof in the event of a copyright dispute; third, through an authentic deed, legal protection can be guaranteed for the parties; fourth, notary authentic deeds can be used as a means of achieving legal goals, namely justice, benefit and legal certainty for the parties who make copyright transfer agreements; fifth, a Notary can have a role as a legal consultant for the parties in making Copyright transfer agreement.